Improving Students’ Speaking Ability Through Shadowing Technique At SMA Negeri 1 Tondano - Rengkung, Gratia; Tuerah, Ignatius J. C.; Lambe, Livianni (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
Speaking is a crucial language acquisition skill, particularly for students learning English as a foreign language (EFL), where many have trouble with vocabulary, pronunciation, and fluency. The purpose of this study is to investigate whether the Shadowing Technique can help grade XI students at SMA Negeri 1 Tondano become more proficient speakers. By using this method, the study aims to enhance students’ fluency, pronunciation, and vocabulary, all of which will enhance their speaking abilities. To evaluate the efficacy of the shadowing technique, this study employed a pre-test and post-test experimental design with a single group. A speaking exam with an emphasis on vocabulary, grammar, fluency, and pronunciation was used to gather data. With the aid of SPSS, reliability, normality, homogeneity, and t-tests were used to analyze the data. After using the shadowing technique, the students’ speaking skills significantly improved, according to the results. With a significant difference (t = -10.591, p < 0.05) in the t-test results, the students’ mean score rose from 47.33 on the pretest to 61.17 on the post-test. These results endorse the inclusion of shadowing techniques in language learning curricula and support their use in enhancing speaking abilities, particularly in fluency and pronunciation.